Trastuzumab in combination with 5‐fluorouracil, leucovorin, oxaliplatin and docetaxel as perioperative treatment for patients with human epidermal growth factor receptor 2‐positive locally advanced esophagogastric adenocarcinoma: A phase II trial of the Arbeitsgemeinschaft Internistische Onkologie Gastric Cancer Study Group. Issue 6 (29th May 2021) - Hofheinz, Ralf‐Dieter; Hegewisch‐Becker, Susanne; Kunzmann, Volker; Thuss‐Patience, Peter; Fuchs, Martin; Homann, Nils; Graeven, Ullrich; Schulte, Nadine; Merx, Kirsten; Pohl, Michael; Held, Swantje; Keller, Ralph; et al.
Abstract: Perioperative chemotherapy with 5‐fluorouracil, leucovorin, oxaliplatin and docetaxel (FLOT) is a mainstay in the treatment of esophagogastric adenocarcinomas (EGA). Trastuzumab improved survival when added to chemotherapy in patients with HER‐2‐positive metastatic EGA. We investigated the combination of trastuzumab and FLOT as perioperative treatment in patients with locally advanced EGA. A multicenter phase II study evaluated the efficacy and toxicity of perioperative FLOT (24‐hours 5‐FU 2600 mg/m 2, leucovorin 200 mg/m 2, oxaliplatin 85 mg/mg 2, docetaxel 50 mg/m 2, trastuzumab 6 mg/kg then 4 mg/kg d1, repeated d15 for four cycles preoperatively and postoperatively followed by 9 cycles of trastuzumab monotherapy) in patients with HER‐2 positive EGA. Patients had ≥cT2, any N, M0 EGA. The primary endpoint was the rate of centrally assessed pathological complete response (pCR). Secondary endpoints comprised disease‐free (DFS) and overall survival (OS), R0 resection rate, toxicity and surgical morbidity. Fifty‐six evaluable patients (median age 62 years) were included; n = 40 had tumors originating from the esophagogastric junction; T stage was (cT2/3/4/unknown): 4/42/8/2; n = 50 patients had cN+ disease. Main adverse events grades 3‐4: leukopenia (17.9%), neutropenia (46.6%) and diarrhea (17.0%). All patients underwent tumor resections. R0 resection rate was 92.9%. Eight patients had anastomotic leakage. One postoperative death occurred. pCR was found in 12 patients (21.4%) and a further n = 14 patients (25.0%) had near complete response. Median DFS was 42.5 months and the 3‐year OS rate was 82.1%. The primary endpoint of achieving a pCR >20% was reached. No unexpected safety issues were observed. Survival data are promising.